ANALISIS FAKTOR- FAKTOR PRIBADI DAN PSIKOLOGI PADA PROSES KEPUTUSAN PEMBELIAN SAYURAN HIDROPONIK DI KOTA PONTIANAK ( STUDI KASUS MEREK SAYOK KITE) - TARYO RIZKIANSAH; DEWI KURNIATI; IMELDA IMELDA (Fakultas Pertanian Universitas Tanjungpura, 2018)
ABSTRAKThis study aims to analyze personal factors (economic situation, lifestyle and values and personality and self-concept) and psychological factors (motivation, perception, learning process and beliefs and attitudes), and indicators that most influence to purchase decision of hydroponic vegetables “Sayok Kite” in Pontianak city. Research methods used quantitative to seek associative relationships that are casual. The sample was chosen by purposive sampling with 150 respondents and data analysis used Konjoin analysis. The results of the analysis in this study showed that the most influential factor is economic situation and the most influential indicator is price befit to quality and service to purchase decision of hydroponic vegetables